Every Move he Makes Jonathan Cope in conversation - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Jonathan Cope in conversation. Cope's ardent partnership with Sylvie Guillem has been one of the great pleasures of the past decade. "I worked with Kenneth on Different Drummer and The Prince of the Pagodas, but I regret that I didn't have a classic MacMillan created on me. I do believe that in the majority of cases, with the MacMillan ballets, the original casts were the best and still are because their character and soul are in the ballet". "I know I got hammered for Carmen. Actually I had some hate mail for that. 'How dare you dance in that music hall piece. You're destroying your career, it's a disgrace'. People tried to take it seriously. And they shouldn't have. People aren't used to seeing me do something different and they don't like it when you try to change your style". PALABRAS CLAVE: Jonathan Cope, life and career.